ESMERALDA --- An Intelligent Satellite for Interactive Graphics - Biering-Sørensen, Stephen; Nielsen, Niels Jørn (DAIMI Report Series, 1977)
This paper gives a functional description of Esmeralda, the satellite part of an interactive graphics host-satellite system. The paper is directed primarily to the reader who wants to know what ESMERALDA is, without having to read the program description and the source text, and wants to design a new host-resident part for the system. ESMERALDA is described in more detail in the authors' masters theses. Readers of type B will find in these theses the detailed information necessary to implement a new host part. They will also find a description of an already existing host part: the WIGGIS system.